INTEGRASI TASAWUF DAN SYARIAH: STUDI KRITIS DISERTASI KARYA NURASIAH, "ASRAR AL-IBADAH, FIKIH SPIRITUAL, DAN PRAKSIS PEMIKIRAN IBN ‘ARABI'". - Hambali, Yoyo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2014)
This paper entitled "Integration of Sufism and Sharia: Criticals Studies of Nurasiah?s Dissertation "Asrar al-Ibadah, Fikih Spiritual, dan Praksis Pemikiran Ibn ?Arabi?. The main source of this article is the dissertation work of Nurasiah and secondary sources consist of manuals/guidelines writing of papers, books research methodology, and other sources relevant to the critical study of this dissertation. This paper concludes that the dissertation work of Nurasiah has several advantages, among others, that in general this dissertation meet the standards as a standard of writing of papers according to the guidelines of writing scientific papers, standard research methodology or research design. This dissertation has the uniqueness and differences with previous research more focused on philosophy and Sufism of Ibn 'Arabi. In the aspect of methodology, in general engineering research, data sources and data analysis used by the compilers of the dissertation so that the general level of reliability and validity can be accounted for. Likewise on the theoretical aspects, in addition to referring to the earlier theories that the authoritative, Nurasiah also formulate his own theory which became frame of mind with the hypothesis that has been demonstrated in research findings. Some shortcomings dissertation Nurasiah between the aspects of methods and approaches, research is lacking Nurasiah in use approach and more precise methods such as not using a legal approach, philosophy, and hermeneutics. Other deficiencies in the study of theory in which the works referenced earlier lacking and the actual (average over 10 years), less equipped with direct quotes and references cited original text, making it hard to be rechecked originality and authenticity